2020
DOI: 10.14309/crj.0000000000000306
|View full text |Cite
|
Sign up to set email alerts
|

Adult-Onset Immunoglobulin A Vasculitis

Abstract: Immunoglobulin A vasculitis (IgAV), formerly Henoch–Schönlein purpura vasculitis, is a vasculitis commonly seen in children and only rarely described in adult patients. IgAV can present as arthralgia, rash, discolored urine, acute kidney injury, and gastrointestinal symptoms. We present a case of a 56-year-old man who presented with 1 month of worsening abdominal pain followed by a bilateral lower extremity rash. Laboratory evaluation indicated an acute kidney injury. Computed tomography and colonoscopy reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…GI manifestations are due to bowel ischemia and edema in the setting of vasculitis and can mimic the presentation of inflammatory bowel disease. These cases are also treated with IV steroids and cyclophosphamide, although severe cases with bowel perforation or infarction require surgical intervention [5,13]. Generally, adults affected by IgA vasculitis experience a more severe progression of the disease and often require more intense treatment approaches.…”
Section: Discussionmentioning
confidence: 99%
“…GI manifestations are due to bowel ischemia and edema in the setting of vasculitis and can mimic the presentation of inflammatory bowel disease. These cases are also treated with IV steroids and cyclophosphamide, although severe cases with bowel perforation or infarction require surgical intervention [5,13]. Generally, adults affected by IgA vasculitis experience a more severe progression of the disease and often require more intense treatment approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal wall edema and thickening cause intestinal obstruction and intussusception. It has been reported that the most commonly affected site is the small intestine, of which the descending duodenum is the most susceptible [9] . The study of Eon Jeong Nam et al stated that the terminal ileum is the most vulnerable, but this is based on adult reports [10] .…”
Section: Casementioning
confidence: 99%
“…IgAV is uncommon in adults but more common in children, accounting for up to 45% of pediatric vasculitides. IgA vasculitis tends to progress more severely in adults, requiring more intensive treatment strategies [ 1 ].…”
Section: Introductionmentioning
confidence: 99%